3D-TECLMOLOGIES IN FORMING AND FOUNDRY - V. S. Doroshenko (Литьë и металлургия)
This review describes metal castings produced using 3D technology. Methods for 3D processing of materials related to the additive method of production, characterized by resource conservation. Frame-cellular casting can inherit the structure of nature with the best combination of materials, durability and attractive appearance. 3D technologies expand the existing range of metal products. Among the new foundry processes at the Institute PTIMA of NAS of Ukraine patented 3D technology of molding sand products through the deformation of granular materials, as well as getting sand shell molds for one-time pattern.